LEGAL PROTECTION FOR DEBTORS AGAINST FORCED EXECUTION OF FIDUCIARY GUARANTEES WITHOUT A CERTIFICATE OF GUARANTEE AT THE LEASING COMPANY - Grace Priskilla Suwanto; Ariawan Gunadi (Jurnal Scientia, 2023)
The financial sector has a major impact on Indonesia's economic development. The consumer community in general also supports this. Due to the high crime rate in the automotive industry, people's demand for motorized vehicles is increasing. Many financial institutions have sprung up that offer low-interest loans and use collateral schemes whereby, if the borrower does not make timely payments, the mortgaged property is returned. Legal processes involving financial institutions are often violated. Registration of trust certificates by financial institutions. Based on the case history, Atjeng Ridwan had to take back his motorbike and two other installments due to late payments to Adira Finance. When Adira's financial officer came to collect the motorbike, the owner was not at Atjeng's house, but Atjeng's sister was forcibly taking the motorbike. A complete record of meeting reliability targets must not accompany recall of motorbikes. Atjeng goes to Adira's finance office to pay the installments, but is charged an additional fee. In this regard, it is necessary to study the legal consequences of PT Adira Finance's actions related to achieving the ultimate goal of guaranteeing. Regulation no. The general manager must request the certification in accordance with 130/PMK.010/2012 Minister of Finance. The expert's conclusion proves that PT Adira Finance has committed an unlawful act and may be subject to administrative sanctions.